Acute complications of elective coronary angioplasty: a review of 500 consecutive procedures. Issue 2 (February 1988) - Steffenino, G; Meier, B; Finci, L; Velebit, V; von Segesser, L; Faidutti, B; Rutishauser, W
Abstract : In 500 consecutive procedures of elective coronary angioplasty attempted at a centre with a primary success of 86%, one or more major acute complications occurred in 34 cases (6.8%). Twenty four patients (4.8%) sustained an acute myocardial infarction (in six this was despite emergency coronary artery bypass surgery) and two patients (0.4%) had emergency coronary bypass without myocardial infarction. Ventricular fibrillation was a complication without sequelae in five (1.0%) patients; one (0.2%) patient died because of refractory ventricular fibrillation and ensuing electromechanical dissociation. "Benign" coronary artery rupture occurred in one (0.2%) patient, and one (0.2%) patient had elective coronary surgery to retrieve the tip of a fractured guide wire after an otherwise successful angioplasty. Despite a low mortality, coronary angioplasty is associated with major complications in about one of 14 procedures; the complication is usually acute myocardial infarction caused by occlusion of the vessel.